INDEPENDENT PAIRS IN FREE BURNSIDE GROUPS - Pahlevanyan, A. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2010)
In this work we prove that for an arbitrary odd $n≥ 1003$ there exist two words $u( x, y), v (x, y)$, almost every images of which in free Burnside group $B (m, n)$ are independent.
Keywords: free Burnside group; independent element; non-amenable group; monomorphism